Chemical Characteristics of the Soot Produced in a High-Speed Direct Injection Engine Operated with Diesel/ Biodiesel Blends (2012)
ABSTRACT: The aim of this work is to study the influence of the molecular structure of fatty acid esters present in biodiesel and their blends with diesel on the chemical characteristics of the emit- ted particulate matter. Biodiesel produced from palm oil, jatropha, castor oil and sachainchi was blended at 5% and 20% by volume with diesel. These fuels were used for the operation of a four-cylinder direct injection automotive diesel engine. The equivalent ratio was kept between 0.36 and 0.40, and the engine was operated at the point of minimum air–fuel ratio and maximum smoke opacity. The amount of particulate matter emitted was evaluated by opacity index. A marked reduction in soot formation was observed when the concentration of unsaturated methyl esters in the fuel was at low concentrations. This was accompanied by a reduction of the aliphatic carbon content in the particulate matter.